Modularly engineering Rhodotorula toruloides for α-terpineol production - Lyu, Liting; Chen, Qiongqiong; Xue, Haizhao; Mustafa, Sumayya; Manzoor Shah, Aabid; Huang, Qitian; Zhang, Yue; Wang, Shuang; Zhao, Zongbao Kent (Frontiers in Bioengineering and Biotechnology, 2024)
α-Terpineol, a monoterpenoid alcohol widely used in the flavor, fragrance and pharmaceutical industries because of its sensory and biological properties. However, few studies have focused on the microbial production of α-terpineol. The oleaginous yeast Rhodotorula toruloides has a natural mevalonate pathway and is a promising host for synthetic biology and biorefinery. The primary objective of this work was to engineer R. toruloides for direct biosynthesis of α-terpineol. The improvement of monoterpenoid production was achieved through the implementation of modular engineering strategies, which included the enhancement of precursor supply, the blocking of downstream pathways, and the disruption of competing pathways. The outcomes of these three methods showed varying degrees of success in enhancing α-terpineol production. The engineered strain 5L6HE5 with competitive pathway disruption and increased substrate supply reached the highest product titer of 1.5 mg/L, indicating that reducing lipid accumulation is an efficient method in R. toruloides for terpenoids synthesis. This study reveals the potential of R. toruloides as a host platform for the synthesis of α-terpineol as well as other monoterpenoid compounds.